Uncovering the Mechanisms of Cryptotanshinone as a Therapeutic Agent Against Hepatocellular Carcinoma - Luo, Yi; Song, Lei; Wang, Xinyu; Huang, Yujie; Liu, Yongqiang; Wang, Qi; Hong, Ming; Yuan, Zhongyu (Frontiers in Pharmacology, 2020)
Hepatocellular carcinoma (HCC) is a fatal and the dominant form of liver cancer without effective and good prognosis treatment so far in clinically. In this study, we explored the anti-tumor effects of cryptotanshinone (CPT) against HCC as well as their molecular mechanisms through a system pharmacology approach and experimental validation. First, we totally obtained 296 targets of CPT and common targets of CPT targets and HCC-related targets. We also elucidated the mechanisms of CPT on HCC through multiple network analysis, including CPT-target network analysis, PPI network analysis, target-function network analysis and pathway enrichment analysis. In addition, we found that CPT induced apoptosis in Huh7 and In conclusion, we first demonstrated the antitumor effect of CPT on Huh7 and MHCC97-H cells both in vitro and in vivo. We revealed the potential antitumor mechanism of CPT that involved the induction of apoptosis and autophagy through inhibition of the PI3K/Akt/mTOR signaling pathway. This paper may provide valuable insight into the clinical application of CPT, serving as a potential candidate agent for HCC.